TRANSFORMASI UMKM GO DIGITAL MELALUI QRIS SEBAGAI PENGGERAK EKONOMI KREATIF DI DESA WISATA SESAOT - Wardhiati, Itriyatul; Jurnal Wicara; Maulida, Meuthia; Wahyuni, Indri; Unsayain, Hazzil; Budastra, I Ketut; Apriani, Maulinda; Santhi, I Gusti; Putri, Dina; Nurardiansyah, Muhammad; Yasmin, Adella; Priadi, Aktory; Nuryadien, Muhammad (Universitas Mataram, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs) has become an essential requirement in the modern economic era, particularly in tourist villages that rely on the creative economy sector. Sesaot Tourism Village, located in West Lombok, holds significant potential in culinary, handicraft, and tourism services; however, it still faces limitations in adopting digital payment technologies. This community service activity aims to improve the digital literacy of MSMEs, encourage the adoption of the Quick Response Code Indonesian Standard (QRIS), and evaluate its impact on business performance. The implementation methods included socialization, technical training, implementation assistance, and impact evaluation. The results showed a significant increase in the number of MSMEs adopting QRIS, rising from 20% before the program to 75% afterward. The positive impacts of QRIS adoption were reflected in transaction efficiency, transparent financial recording, an average revenue increase of 15–20%, and higher customer satisfaction among tourists. These findings highlight QRIS as a key driver of MSME digital transformation and a catalyst for strengthening the creative economy in Sesaot Tourism Village.